Opportunity and outcome: A quantitative evaluation of the stem extended curriculum programme at a research-intensive university - Mouton, M.; Rewitzky, I.M. (South African Journal of Higher Education, 2024)
Higher education plays a significant role in economic development. The significant growth in the South African higher education system, which nearly doubled since 1994, is therefore promising for long–term economic growth and development. The country further recognised that teaching and assessment practices in higher education needed to adapt to address the needs of thousands of underserved students, to achieve parity in educational outcomes for all students. One intervention to achieve this goal was the founding of the Extended Curriculum Programmes (ECPs) – a systemic intervention to facilitate equitable access and success in higher education, intending to create a curriculum space where talented students that may be underprepared for the challenges associated with studies in higher education, could achieve solid foundations for academic success. This article explores the opportunity and outcome offered by an ECP at a research–intensive university in South Africa over seven cohorts (2010–2016). The main contribution to the research on the criteria of equitable access and success is evidence of the progress that has been made in the outcomes of the STEM ECPs over the last 10 years. The programme has delivered a significant number of additional graduates and postgraduates over the seven years to the three STEM faculties. Moreover, the cohorts included a demographic distribution much closer aligned to the country’s demographics, at enrolment as well as graduation, and included a considerable number of female students of all demographic groups. This STEM ECP has therefore facilitated access and success in higher education for a significant number of students from diverse backgrounds via an alternative, enriched route.